Conflicts of interest in the context of implementing the CSR concept in hotels - Kurowska, Ewelina (Konflikty interesów w kontekście realizacji koncepcji CSR w hotelach, 2021)
The purpose of the article is to identify and characterize conflicts of interest in hotels in the context of implementing the CSR concept. The study, based on the subject literature review, presents the essence of conflicts of interest, their reasons, types in organizations and the concept of corporate social responsibility (CSR) and the characteristics of stakeholders. The subsequent sections were developed as a result of participant observation and the author’s experience as an employee of a hotel enterprise. The concept of a hotel was explained, its stakeholders were characterized and their expectations in the context of the CSR concept. The final section discusses the types of conflicts of interest occurring between stakeholder groups in a hotel. The analysis showed that the implementation of the CSR concept in hotels is associated with conflicts of interest. However, relevant entrepreneurial knowledge based on the reliable identification of stakeholders and their expectations, as well as the efficient process of communication with them, allows for avoiding some conflicts or solving them effectively and quickly
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 57-71